2022
DOI: 10.1039/d1nr05906h
|View full text |Cite
|
Sign up to set email alerts
|

Role of the microridges on cactus spines

Abstract: Cactus spines have inspired a wide range of micro- and nano-structures that cause droplets to move spontaneously and directionally. The conical shape and the surface wettability gradient are two typical...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Based on the research by many scientists regarding how it collects water, is has been found that its spines with HS ensure its fundamental life in extremely harsh external environments, such as highly arid deserts. 75 Ju et al 36 investigated the microstructure of the spines of cactus in detail. The SEM image (Fig.…”
Section: Cactusmentioning
confidence: 99%
“…Based on the research by many scientists regarding how it collects water, is has been found that its spines with HS ensure its fundamental life in extremely harsh external environments, such as highly arid deserts. 75 Ju et al 36 investigated the microstructure of the spines of cactus in detail. The SEM image (Fig.…”
Section: Cactusmentioning
confidence: 99%
“…During fog collection, fog first condenses at two positions of the directional barb and gradient groove of the cactus, and then moves backward along the directional barb and gradient groove until absorbed by the tail trichome as shown in Figure d . Research on the structure of the cactus fog collection has contributed to the development of new efficient fog collection materials and equipment. A bionic hair-like composite coating is prepared by spraying magnetic particles and resin to build a hierarchical structure, using 1H, 1H, 2H, 2H perfluorodecyltriethoxysilane to reduce surface energy, as shown in Figure e and f . This bionic hair-like composite coating exhibits good fog collection performance.…”
Section: Bionic Fog Collection Surfacesmentioning
confidence: 99%
“…[13][14][15] To enhance the water transportation velocity, researchers devoted many effective works and found that the surface with a structure gradient could also realize the SDWT and that the water transportation velocity was greatly enhanced. [16][17][18][19][20] When a water droplet is placed at the narrow side of the superhydrophilic single wedge-shaped pattern which has a structure gradient, it would be quickly caught by the narrow side of the pattern and then spontaneously and directionally transported to the wide side of the pattern under Laplace pressure. 21 Although the superhydrophilic single wedge-shaped pattern successfully demonstrated the transportation capability in the SDWT, the Laplace pressure difference of the water droplet significantly decreased due to the large end size, which meant that the single wedgeshaped pattern was not suitable for long-distance water transportation.…”
Section: Introductionmentioning
confidence: 99%